2019
DOI: 10.3390/v11070586
|View full text |Cite
|
Sign up to set email alerts
|

Two Phages of the Genera Felixunavirus Subjected to 12 Hour Challenge on Salmonella Infantis Showed Distinct Genotypic and Phenotypic Changes

Abstract: Salmonella Infantis is considered in recent years an emerging Salmonella serovar, as it has been associated with several outbreaks and multidrug resistance phenotypes. Phages appear as a possible alternative strategy to control Salmonella Infantis (SI). The aims of this work were to characterize two phages of the Felixounavirus genus, isolated using the same strain of SI, and to expose them to interact in challenge assays to identify genetic and phenotypic changes generated from these interactions. These two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 78 publications
(143 reference statements)
0
18
1
Order By: Relevance
“…These three tests form the basis for the initial screening of a phage library to identify phages with the broadest host range. The data generated also allowed direct comparison of DST versus EOP, as these two assays are commonly used to characterise phages ( Sybesma et al, 2016 ; Montso et al, 2019 ; Rivera et al, 2019 ; Supplementary Tables S5 , S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…These three tests form the basis for the initial screening of a phage library to identify phages with the broadest host range. The data generated also allowed direct comparison of DST versus EOP, as these two assays are commonly used to characterise phages ( Sybesma et al, 2016 ; Montso et al, 2019 ; Rivera et al, 2019 ; Supplementary Tables S5 , S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…These three tests form the basis for the initial screening of a phage library to identify phages with the broadest host range. The data generated also allowed direct comparison of DST versus EOP, as these two assays are commonly used to characterise phages (Montso et al, 2019; Rivera et al, 2019; Sybesma et al, 2016) [Supplementary Data Table S5 & S6].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, felixounaviruses were identified 33 times in samples from no less than 23 WWTPs, indicating that they are ubiquitous in the Danish wastewater environment and that they are easily cultivated, though the method prevents assessment of relative preponderance. Felixounaviruses often have broad within-genus host ranges, and isolates have been shown to be able to rapidly expand their host range when challenged, co-coinciding with mutations in the long tail gene [57,58]. Five of the Myoviridae are members of the newly announced genus Phapecoctavirus with substantial similarity (86-90%, BLAST) to the type species Escherichia phage phAPEC8 (JX561091) [23,59].…”
Section: Fifty-five Myoviridae Speciesmentioning
confidence: 99%